Acute Chagas Disease in northeastern Brazil: epidemiology and temporal evolution (Research, Society and Development, 2020)
This study evaluated the epidemiological situation and the profile of the reported and confirmed cases of acute Chagas' disease (ACD) in the Northeast, demonstrating sociodemographic indicators, transmission scenarios and evolution. This study aims to evaluate the epidemiological situation and the profile of reported and confirmed cases of acute Chagas disease (ACD) in the Northeast. This is an exploratory, descriptive, retrospective and quantitative study, developed from the confirmed cases of ACD reported in Northeastern Brazilian states from 2007 to 2017. Information was collected from the Information System of Notification Offenses (SINAN). The following variables were selected: region and UF (federation unit), month of the 1st symptom, pregnant women, race, area of residence, gender, schooling, age group, mode and probable place of infection, confirmation criteria and clinical evolution. There were 2330 cases of ACD in the period throughout the national territory. The North region had 95.12% of the cases. Following, the Northeast region with 2.91% and average annual incidence of 0.011 cases per hundred thousand inhabitants. The predominance presented was in the age group of 20 to 59 years old and living in the rural area. The most frequent mode of infection was oral and the confirmation criterion was laboratory and with good clinical evolution. The understanding of the different epidemiological scenarios of Chagas' disease and its transmission dynamics is a crucial element for the elaboration of consistent and sustainable actions of surveillance, health care and management of strategies to combat disease.